2008
DOI: 10.1249/mss.0b013e318158b504
|View full text |Cite
|
Sign up to set email alerts
|

Gait Speed and Step-Count Monitor Accuracy in Community-Dwelling Older Adults

Abstract: All three objective activity monitors performed well at moderate and higher walking speeds, but at decreased gait speeds, the SAM seemed to be the most accurate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
118
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(127 citation statements)
references
References 32 publications
7
118
2
Order By: Relevance
“…The SAM is a pager sized accelerometer worn around the ankle using a Velcro strap [6][7][8][9]. It provides no feedback to the wearer and is impervious to tampering.…”
Section: Assessment Of Ambulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The SAM is a pager sized accelerometer worn around the ankle using a Velcro strap [6][7][8][9]. It provides no feedback to the wearer and is impervious to tampering.…”
Section: Assessment Of Ambulationmentioning
confidence: 99%
“…Time spent sitting or lying affects muscle physiology [4], is thought to accelerate sarcopenia [5], and to be a determinant driver of the obesity epidemic [6]. These two effects of SB: obesity and low muscle strength appear to potentiate each other to increase risk of disablement and frailty in older adults [7].…”
mentioning
confidence: 99%
“…Some reports have indicated that a pedometer or accelerometer may underestimate the actual steps taken by elderly people who have disease and walk at a slow speed, as with the subjects in this study (Storti et al, 2008;Elsworth et al, 2009). However, it has also been reported that a triaxial accelerometer would be better suited than a pedometer to count shuffling steps and slow speed, such as patients with Parkinson's disease (Dijkstra et al, 2008) and, furthermore, that a piezoelectric sensor can accurately calculate the number of steps taken by an individual at slow speed (Melanson et al, 2004).…”
Section: Daily Ambulatory Activitymentioning
confidence: 59%
“…We evaluated three dependent variables (Storti et al, 2008): (a) the number of VM counts per day, which we interpreted as the total force applied on each day of testing; (b) the total number of steps per day; and (c) for each day, the mean number of VM counts/step, which we interpreted as the resultant force per step.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we used wireless accelerometry to evaluate daily variations in gait before and during a sea voyage. Wireless accelerometry is a recent technology that has been validated as a monitor of human locomotor activity 88 in settings outside the laboratory (Cavanaugh, Kochi, & Stergiou, 2010;Storti et al, 2008).…”
mentioning
confidence: 99%